The Effect of Mesenchymal Stem Cell Wharton Jelly on Alzheimer’s Rat with Y-Maze Test Method - Sisca Dwi Yarni; Hirowati Ali; Djong Hon Tjong (Majalah Kedokteran Andalas, 2021)
Objective: This study aims to examine the y-maze test in alzheimer's rat after giving mesenchymal stem cell wharton jelly. Methods: This study used the y-maze test method to test the cognitive test of rat with the Y arm model. The treatment group consisted of a control, AlCl3, MSC-WJ and a combination of AlCl3 and MSC-WJ. The results obtained were analyzed in the form of a percentage. Results: The results of this study showed that the y-maze test showed that MSC-WJ had a significant effect compared to the AlCl3 control group in the alzheimer’s rat, namely 51.33% and 12.31%. Conclusion: In this study it was concluded that that MSC-WJ has a significant effect on alzheimer’s rat with y maze test.Keywords: AlCl3; Alzheimer’s; Mesenchymal Stem Cell Wharton Jelly